2015
DOI: 10.1007/s10530-015-0850-2
|View full text |Cite
|
Sign up to set email alerts
|

Part of the solution? Stakeholder awareness, information and engagement in tree health issues

Abstract: The dangers posed to wooded environments from tree pests introduced by the expansion of international trade in live plants and the continued use of wood packaging in transporting materials have been widely accepted. A lack of awareness of the issues amongst key stakeholders involved in the movement of these materials can hamper an effective response as their unaltered behaviours continue to have unintended consequences. Better communication and engagement is needed to enrol this wider range of actors, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 49 publications
3
69
0
1
Order By: Relevance
“…More positively, increased awareness is likely to improve surveillance and pest monitoring, at the same time as increasing outbreak preparedness. A lack of awareness of plant biosecurity practices and risks amongst forestry, horticulture and conservation sector stakeholders is commonly suggested (Webber 2010;Dehnen-Schmutz et al 2010) and Marzano et al (2015) emphasise that raising awareness amongst these stakeholders is essential for future biosecurity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More positively, increased awareness is likely to improve surveillance and pest monitoring, at the same time as increasing outbreak preparedness. A lack of awareness of plant biosecurity practices and risks amongst forestry, horticulture and conservation sector stakeholders is commonly suggested (Webber 2010;Dehnen-Schmutz et al 2010) and Marzano et al (2015) emphasise that raising awareness amongst these stakeholders is essential for future biosecurity.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on awareness of tree pests and diseases generally are rare and very little work has been done around awareness of forestry-related professionals (Hathaway et al 2003;Hurley et al 2012). A comprehensive review of the literature on stakeholder awareness relating to tree health identified only eight studies focused directly on tree pests (Marzano et al 2015). Seven of these looked at awareness of beetle pests while one study looked at the Sirex woodwasp (Sirex noctilio).…”
Section: Introductionmentioning
confidence: 99%
“…Stakeholders' participation in forestry decisionmaking, which was not a usual practice in the traditional forestry, might be particularly beneficial by providing regional expertise and increasing the legitimacy to the final outcome (Beckley et al 2005) and strength interest of diverse stakeholder groups to participate in final strategy (Phalen 2009;O'Brien et al 2013;Shackelford et al 2013;Sarvašová et al 2014;Marzano et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…It seems that voters and lawmakers would support strong actions because, as it is, the enormous costs of invasive forest pests tend to fall on private citizens and municipal governments who lack the means to pay (Lovett et al 2016). One pathway to limiting invasions is increasing public awareness of the problem and the solutions (Marzano et al 2015;Klapwijk et al 2016). New Zealand, which is a global model for limiting biological invasions, has exceptional biosecurity partly because of strong national will to do so, which is itself a product of high awareness by citizens of the socioeconomic costs of invasives (Goldson et al 2015).…”
Section: Improved Biosecurity Against Future Human-aided Invasionsmentioning
confidence: 99%